Histologic evaluation of the effect of nicotine administration on bone regeneration: a study in dogs Avaliação histológica do efeito da nicotina sobre a regeneração óssea: estudo em cães - Juliana Bezerra Saldanha; Suzana Peres Pimentel; Marcio Zaffalon Casati; Antonio Wilson Sallum; Enilson Antonio Sallum; Francisco Humberto Nociti Júnior (Sociedade Brasileira de Pesquisa Odontológica, 2004)
The objective of this study was to investigate the histometric impact of nicotine on bone regeneration of surgically created alveolar ridge defects in dogs. Sixteen mongrel dogs were used. One defect was surgically created unilaterally in the mandible, and left to heal spontaneously. The animals were randomly assigned to one of the following groups: Group 1 - control (n = 8) and Group 2 - subcutaneous nicotine administration (2 mg/kg) twice a day (n = 8). After 4 months, the animals were sacrificed and the specimens routinely processed for semi-serial decalcified sections. Bone height (BH), bone width (BW), bone density (BD), and bone area (BA) of the newly-formed bone were evaluated. Intergroup analysis (Mann-Whitney rank sum test) showed that regardless of the presence of nicotine, no significant differences were observed regarding bone width (BW), bone area (BA) and bone height (BH) (p > 0.05). On the other hand, it was demonstrated that nicotine administration significantly influenced the proportion of mineralized tissue within the limits of the newly-formed bone (BD) (p < 0.001). Within the limits of the present study, it can be concluded that nicotine might affect but not prevent bone healing in defects left to heal spontaneously. O objetivo do presente estudo foi avaliar histometricamente a influência da nicotina sobre a regeneração óssea de defeitos criados cirurgicamente em rebordos alveolares edêntulos de cães. Defeitos ósseos foram criados cirurgicamente em um dos lados da mandíbula de dezesseis cães e foram deixados para que curassem espontanea-mente. Os animais foram aleatoriamente designados para um dos seguintes grupos: Grupo 1 - controle (n = 8) e Grupo 2 - administração subcutânea de nicotina (2 mg/kg) duas vezes ao dia durante 4 meses (n = 8). Os animais foram sacrificados, e secções semi-seriadas descalcificadas, obtidas. Os parâmetros histométricos avaliados foram altura, largura, área e densidade do tecido ósseo neoformado. A análise intergrupos (Mann-Whitney "rank sum test") demonstrou que a administração de nicotina não influenciou altura, largura e área de tecido ósseo neoformado (p > 0,05). Entretanto, a administração de nicotina influenciou significativamente a densidade do tecido ósseo neoformado (p < 0,001). Dentro dos limites do presente estudo, pode-se concluir que a nicotina pode afetar, mas não impedir a regeneração de defeitos ósseos criados cirurgicamente em mandíbulas edêntulas de cães.